Imaging of hypochlorous acid in mitochondria using an asymmetric near-infrared fluorescent probe with large Stokes shift. Issue 37 (8th September 2022) - Hu, Wei; Qiang, Taotao; Li, Chenchen; Ren, Longfang; Cheng, Fei; Wang, Baoshuai; Li, Mingli; Song, Xinjian; James, Tony D.
Abstract : Small-molecule near-infrared (NIR) imaging facilitates deep tissue penetration, low autofluorescence, non-invasive visualization, and a relatively simple operation. Abstract : Small-molecule near-infrared (NIR) imaging facilitates deep tissue penetration, low autofluorescence, non-invasive visualization, and a relatively simple operation. As such it has emerged as a popular technique for tracking biological species and events. However, the small Stokes shift of most NIR dyes often results in a low signal-to-noise ratio and self-quenching due to crosstalk between the excitation and emission spectra. With this research, we developed a NIR-based fluorescent probe WD-HOCl for hypochlorous acid (HOCl) detection using the NIR dye TJ730 as the fluorophore, which exhibits a large Stokes shift of 156 nm, with no crosstalk between the excitation and emission spectra. It contains acyl hydrazide as the responsive group and a pyridinium cation as the mitochondria-targeting group. The fluorescence intensity of WD-HOCl was enhanced by 30.1-fold after reacting with HOCl. Imaging studies performed using BV-2 cells indicated that WD-HOCl could be used for endogenous HOCl detection and imaging in living cells exposed to glucose and oxygen deprivation/reperfusion. Finally, we demonstrated that inhibiting the expression of NOX2 reduced the HOCl levels and the severity of oxidative stress during stroke in a mouse model.